Player Experience Measurements Using Immerse Experience Questionnaire on Pewayangan Game - Rizza Indah Mega Mandasari; Bambang Pudjoatmodjo (IJAIT (International Journal of Applied Information Technology), 2019)
Wayang is an Indonesian heritage that becomes the world's heritage based on the recognition of UNESCO on 7 November 2003. However, the establishment of the wayang as a world cultural heritage does not make it is recognized by the young generation in Indonesia. They considered that wayang is only as a conventional culture, the duration is too long, and it tends to be boring. Creative and interactive media are needed to attract the younger generation to wayang, one of them is using the game. A Game is an interactive media that is much liked by all ages because they are entertaining, challenging, and fun. In the development of a game, it needs to emphasize a good user experience. The measurement of user experience in the game called the gameplay experience. This paper discussed the measurement gameplay experience (GX) using Immerse Experience Questionnaire (IEQ) on Wayang Game. The results of GX measurements become a benchmark for the quality of the game ‘pewayangan’ in attracting the young generation.